(untitled) (Experimental biology, 2025)
To date, myco- and lichenobiota of Mangistau region are practically unstudied, only 5 species of fungi and fungus-like organisms have been recorded here. In this connection, the aim of our work was to study the species composition of myco- and lichenobiota of Mangistau region and to make an annotated list of species. Specimens for the article were collected in 2024 in the territory of Mangistau region. Preparation of specimens of fungi and lichens .As a result of processing of literature data and herbarium specimens, an annotated list of fungi, fungus-like organisms and lichens of Mangistau region including 102 species from two kingdoms Chromista and Fungi was compiled. The value and practical significance of our study lies in obtaining data on the species composition of myco- and lichenobiota of Mangistau region, distribution of fungi and lichens, their ecological groups and confinement to different types of substrates.